Mitigating the impact of oil‐palm monoculture on freshwater fishes in Southeast Asia. Issue 5 (19th March 2015) - Giam, Xingli; Hadiaty, Renny K.; Tan, Heok Hui; Parenti, Lynne R.; Wowor, Daisy; Sauri, Sopian; Chong, Kwek Yan; Yeo, Darren C. J.; Wilcove, David S.
Abstract Anthropogenic land‐cover change is driving biodiversity loss worldwide. At the epicenter of this crisis lies Southeast Asia, where biodiversity‐rich forests are being converted to oil‐palm monocultures. As demand for palm oil increases, there is an urgent need to find strategies that maintain biodiversity in plantations. Previous studies found that retaining forest patches within plantations benefited some terrestrial taxa but not others. However, no study has focused on aquatic taxa such as fishes, despite their importance to human well‐being. We assessed the efficacy of forested riparian reserves in conserving freshwater fish biodiversity in oil‐palm monoculture by sampling stream fish communities in an oil‐palm plantation in Central Kalimantan, Indonesia. Forested riparian reserves maintained preconversion local fish species richness and functional diversity. In contrast, local and total species richness, biomass, and functional diversity declined markedly in streams without riparian reserves. Mechanistically, riparian reserves appeared to increase local species richness by increasing leaf litter cover and maintaining coarse substrate. The loss of fishes specializing in leaf litter and coarse substrate decreased functional diversity and altered community composition in oil‐palm plantation streams that lacked riparian reserves. Thus, a land‐sharing strategy that incorporates the retention of forested riparian reserves may maintain the ecological integrity of fish communities in oil‐palm plantations. We urge policy makers and growers to make retention of riparian reserves in oil‐palm plantations standard practice, and we encourage palm‐oil purchasers to source only palm oil from plantations that employ this practice.